Lattice oxygen activation in disordered rocksalts for boosting oxygen evolution. Issue 5 (18th January 2023) - Zhao, Menghan; Zheng, Xuerong; Cao, Chengchi; Lu, Qi; Zhang, Jinfeng; Wang, Haozhi; Huang, Zhong; Cao, Yanhui; Wang, Yang; Deng, Yida
Abstract : Lattice oxygen could participate in catalyzing oxygen evolution reaction via the lattice oxygen oxidation mechanism, which provides the possibility of exploring electrocatalysts to overcome the scaling relationship in adsorbate evolution mechanism. Abstract : The recent development of some special oxygen evolution reaction (OER) electrocatalysts shows that the lattice oxygen could participate in the catalysis process via the lattice oxygen oxidation mechanism (LOM), which the provides good possibility of exploring advanced electrocatalysts that could overcome the scaling relationship in conventional catalysis processes through a traditional adsorbate evolution mechanism. In this work, we theoretically predict that, benefiting from the unhybridized O–Li orbitals and the resulting metastable Li–O–Li ligands, the lattice oxygen could be easily activated and oxidized at relatively high oxidation voltages. Thus, lithium-excess disordered rocksalts (DRX) should possess the potential for acting as active OER electrocatalysts, which catalyze through the LOM pathway. The isotope labelling experimental results show that the lattice oxygen in the DRX was activated and participated in the OER process through the LOM pathway. The typical DRX of Li1.2 Fe0.4 Ti0.5 O2 displays obviously pH-dependent OER activity under the LOM process and shows a low overpotential of 263 mV to reach 10 mA cm −2 with long-term stability for 100 hours. The turnover frequency of Li1.2 Fe0.4 Ti0.5 O2 is nearly 9 times that of LiFePO4 at the overpotential of 300 mV. This work opens a new chemical space for exploring efficient electrocatalysts to enhance the OER performance through the LOM pathway.